Seroprevalence of HIV, HBV, HCV and Syphilis among Blood donors at a tertiary care hospital - Bindu Madhavi R; Hanumanthappa A R; Vishwanath G (Journal of Clinical and Biomedical Sciences)
Introduction: Blood transfusion is a lifesaving essential therapeutic procedure in many medical and surgical instances, as there is no genuine substitution. Even though it can save many human lives, in some instances it can transmit infectious diseases which are fatal. Amongst the undesirable complications due to blood transfu-sion, transmission of certain Transfusion Transmissible Infections (TTIs) like HIV, HBV, HCV and Syphilis are the most significant long term detrimental side effects. Hence meticulous pre transfusion testing and screening particularly for TTIs is the need of the hour. Objectives: To determine the prevalence and trend of HIV, HBV, HCV and Syphilis among the blood donors. Materials and Methods: The study was done at Blood bank, Chigateri District Hospital, attached to J J M Medical College, Davangere. Data was collected for a period of 5 years, from January 2010 to December 2014. All the blood samples were screened for HIV, HBV and HCV by ELISA and Syphilis by Rapid Plasma Reagin test (RPR). Results: A total of 27, 300 blood donors were screened during the study period, out of which 85.5% were voluntary donors and 14.5 % were replacement donors. Among the blood donors screened, seroprevalence of HIV, HBV, HCV and Syphilis was 0.25 %, 1.99 %, 0.02 % and 0.004 % respectively. Conclusion: Blood transfusion should be strictly done only during an absolute need. To give utmost importance to continue screening donated blood, with highly sensitive and specific tests and to counsel positive donors for any above infections. Keywords : Transfusion Transmitted infections , Human immunodeficiency virus , Hepatitis B virus , Hepatitis C virus , Syphilis , Blood donors